FROM POST OFFICE TO PUBLIC COMMUNICATION POINTS: A STUDY ON THE SPATIAL TRANSFORMATION OF PUBLIC BUILDINGS DUE TO DECREASING FUNCTIONALITY WITH REGARD TO RECENT DEVELOPMENTS IN INFORMATION TECHNOLOGY - Esin, Simge; Ozcan, Oguzhan (LOCKE SCIENCE PUBL CO INC, 2010)
The classical structure of postal services and post offices, which was fully established in the 17th century, is losing its value and importance because of developments in information technology; however, these physical public spaces must be sustained to support national strategies. Using Public Communication Point (PCP) criteria, it is possible to determine which post offices with decreasing functionality must be preserved. Using the results of the analysis of the criteria, we can determine the communicational demands of the regions where the post offices are located and develop spatial organizations for each post office. This paper addresses the research regarding this idea by examining 99 post offices in 14 different groups in Istanbul.
Keywords: Environmental Sciences & Ecology; Public Administration; Urban Studies